Improvement of Children's Education through Acehnese Coastal Women's Work Ethic in Family Economic Stability - Firdaus M Yunus; Husna Amin; Raina Wildan; Azwarfajri Azwarfajri; Masrizal Masrizal (AL-ISHLAH: Jurnal Pendidikan, 2023)
This research aims to observe the roles women in coastal Aceh play in bolstering family income and their own efforts to support children's education. This research was conducted in the field using a qualitative descriptive methodology. This research set out to learn how hard women in Keude Unga, Cebrek, and Gampong Meunasah Tuha work to improve their households' financial situations and reduce poverty in their communities. Participant observation, in-depth interviews with targeted informants, and document analysis were the three phases of the data collection procedure. The study's findings show that women from Aceh have a robust work ethic when it comes to supporting children's education. There is a multitude of activities within the public realm that serve as evidence of this strong commitment to labour. The contemporary understanding of work ethic necessitates an examination of the historical presence and circumstances of women. The manifestation of women's work ethic may be observed in the coastal communities of Keude Unga, Meunasah Tuha, and Cebrek, where the entire population faces the arduous task of improving their socioeconomic status and providing for their families.